Penerapan Model Pembelajaran Berbasis Masalah Pada Materi Bumbu Dasar dan Turunannya di SMKN 2 Mojokerto - Dewi Nur Inayah; Asrul Bahar; Ila Huda Puspita D; Lucia Tri Pangesthi (Jurnal Bintang Pendidikan Indonesia, 2023)
This study aims to determine the effect of applying the problem-based learning model with the following research variables: (1) teacher activity; (2) student activities; (3) students’ cognitive learning outcomes; and (4) students’ responses by applying the Problem-Based learning model to the Basic Spices material and their Derivatives. This research was conducted in class X Culinary 3 SMKN 2 Mojokerto. This type of research is quasi-experimental or quasi-experimental. This research was applied to class X Culinary 3 with a total of 33 students. The data in the study were obtained by several methods, namely: observation, written test (pre-test, post-test), and questionnaires. The data analysis technique used the Paired Sample T-Test. The results of the study show: (1) the teacher’s activities are in the very good category; (2) student activity is in very good category; (3) Resultspre-testand the student post-test with paired t test showed a significant value of 0.001 <0.005; (4) student responses are in very good category.